Corrosion wear characteristics of TC4, 316 stainless steel, and Monel K500 in artificial seawater. Issue 38 (3rd May 2017) - Jun, Chen
Abstract : Wear-induced corrosion can accelerate material degradation, and the passive film in the wear track is only partially destroyed. Abstract : The corrosion wear behaviors of TC4, 316 stainless steel, and Monel K500 in artificial seawater were systematically investigated in this study. The contribution of corrosion and wear on corrosion-wear synergism and damage-recovery process of passive film for the three alloys were addressed. It can be concluded that wear loss for these three alloys at cathodic polarization was lower than that at anodic polarization and OCP. The passive film was damaged due to mechanical wear, resulting in low OCP and high corrosion rate. Electrochemical test showed that the passive film in the wear track area was only partially destroyed during the corrosion wear test. The ratio of the actual damage area in the wear track S e / S m of 316 stainless steel and TC4 was much larger than that of Monel K500.